Effect and Mechanism of Yisui Fuyongtang (YSFYT) Decoction on Cognitive Function and Synaptic Plasticity in Rats with Vascular Cognitive Impairment - Tingliang Gong; Zhaoliang Luo; Li Huang; Caixian Xiao; Junlu Yi; Junfeng Yan; Qian Chen; Weihong Li; Wenqiang Tao (Journal of Immunology Research)
Vascular cognitive impairment (VCI) has emerged as the second major disease responsible for dementia, and there is still a lack of effective treatment methods for this disorder to date. Clinical medications have found that Yisui Fuyongtang (YSFYT) Decoction is effective in improving neurological signs and learning-memory functions in patients who develop white matter lesions and whole brain atrophy. To clarify the effect and molecular regulation mechanism of YSFYT Decoction on model rats, this research analyzed the influence of YSFYT Decoction on the learning-memory ability and lipid metabolism of rats based on behavioral and biochemical analysis. Further pathology and protein detection methods were adopted to investigate the action of YSFYT Decoction on the neurons in the hippocampus of model rats and the regulation of the brain derived neurotrophic factor (BDNF)-tyrosine protein kinase receptor B (TrkB) signaling pathway. Compared with the VCI group, after YSFYT Decoction administration, the ratio of swimming time in the platform, number of crossing the platform, number of active avoidance, and proportion of active avoidance of the rats were markedly increased, whereas the response latency was substantially reduced (p<0.05). Biochemical tests indicated that contents of lipoprotein lipase (LPL), triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) of the model rats in YSFYT Decoction treatment group were greatly reduced, whereas those of total antioxidant capacity (T-AOC), glutathione peroxidase (GSH-PX), catalase (CAT), malondialdehyde (MDA), and superoxide dismutase (SOD) were elevated (p<0.05). Additionally, Bcl-2 expression in YSFYT Decoction treatment group was significantly increased, but neuron apoptosis of the hippocampus tissue was reduced. Meanwhile, neuron number was apparently higher than that in VCI model group. Following Yisui Decoction treatment, expressions of growth-associated protein 43 (GAP43), synaptophysin (SYP), postsynaptic density 95 (PSD95), NMDAR subunit 2B (NR2B), BDNF, TrkB, phospho-mitogen-activated protein kinase (p-MAPK), extracellular signal-regulated kinase (ERK), phosphatidylinositol 3-kinase (PI3K), and phospho-protein kinase B (p-AKT) were markedly elevated. Taken together, YSFYT Decoction could activate the BDNF-TrkB signaling pathway, elevate Bcl-2 expression, and minimize neuronal apoptosis in hippocampus, thereby improving the behavioral characteristics and biochemical indicators of the VCI rat model.